Geophysical investigation for mineral prospect in Igbeti-Moro area, Southwestern Nigeria - Olasunkanmi, Nurudeen Kolawole; Lukman A. Sunmonu; Moruffdeen A. Adabanija (Kuwait Journal of Science, 2020)
To establish significant geologic features associated with the marble, gabbro and muscovite mineralization in Igbeti-Moro area, within southwestern Nigeria, the high-resolution aeromagnetic data were subjected to data enhancement processes and interpretation. The reduced-to-magnetic equator (RTE) anomaly map was subjected to various normalized (vertical, tilt and total horizontal) derivatives for lineament enhancement, edge detection of analytic signal (AS) amplitude and depth estimation techniques of source parameter imaging (SPI), average power spectrum and magnetic source depths were estimated using the source parameter imaging averaged power spectrum and Euler deconvolution at different spectral indices. The range of RTE residual magnetic intensity from 338.3 nT to -2.4 nT (low), 9.9 to 27.7 nT (intermediate) and 32.1 to 208.0 nT (high) revealed the three major lithologies in the area which include the: Pan African Granite, early metamorphic tectonites, metasedimentary rocks and the intrusion of quartz and amphibolite schists. The prominent NE – SW lineament revealed regional structural grains (fractures and faults) in these rocks associated with emplacement of the quartz-schist and muscovite-schist, which would have formed contemporaneously with isoclinal fold and hosts marble, gabbro, amphibolites, and muscovite mineralogy at shallow depth range 0 to 200 m in the western, north central and northeastern parts of the area. The significant geologic features and their geometry of occurrences have been established as a prospect for solid minerals in the area. However, geochemical investigation is encouraged to determine the economic value of the minerals. Keywords: geologic features; lineament; mineralogy; magnetic anomalies; regional structural grains.